Similarities and differences in the process of automating the assembly of rigid bodies and elastic elements of pneumatic tires - Knast, Paweł (Technologia i Automatyzacja Montażu (Assembly Techniques and Technologies), 2021)
The paper presents the classification of tyre elements intended for automatic and robotic assembly into rigid bodies (material points within the geometric part of the element cannot move against each other) and plastic elements (subject to irreversible deformation under the influence of external forces, temperature, gravity, which act on the unvulcanised tyre elements). The assembly process has been divided into 7 closed-loop areas of the automation and robotisation process of industry 4.0 factories in order to demonstrate the similarities and differences that affect the degree of automation and robotisation of assembly. Characteristic features of rigid bodies and plastic elements are also described. Plastic elements of the tyre prior to vulcanization are characterized by internal friction due to shifting of its individual layers in relation to one another. The placement of layers has a major impact on the selection of technology, machines and instrumentation necessary for the automation and robotisation of production processes in modern factories and logistics centres. The author presents several examples of physical and geometric features facilitating the automation of rigid bodies and plastic elements assembly, as well as their positioning on the machine in the process of multi-layer tyre production. The multi-layer nature of pneumatic tyres determines the process of designing automatic and robotic assembly stations, which is only possible after the completion of the tyre design. This is an Open Access article distributed under the terms of the Creative Commons Attribution License CC BY 4.0 (https://creativecommons.org/licenses/by/4.0/)